Hydrogeochemical assessment of the Jeffrey’s arch domain, Eastern Cape, South Africa - Tshishonge, Vhuthu (My University, 2021)
The Jeffreys Arch domain consists of groundwater schemes that contribute towards the Algoa Water Supply System through springs and borehole development. The Kabeljous River catchment is subject to over-abstraction for agricultural activities, mainly for commercial irrigation. A hydrogeochemical assessment of the domain is presented using physicochemical, major ion and stable isotopes of oxygen-18 and deuterium methods. The geology comprises of the Table Mountain Group quartzite, Bokkeveld Group shale, and miniature Grahamstown Formation silcretes. Quartz and feldspar are the main minerals that constitute the rocks. The hydrochemical facies in the study area is represented by the Na-Cl type water. Groundwater is primarily acidic to slightly alkaline leading to accelerated leaching of metals such as iron and manganese prevalent in the domain. The Bokkeveld shale aquifer showed a greater salinity concentration than the TMG aquifers. Elevated salinity and sulphate concentrations downstream of the Kabeljous River signify the contribution of irrigation return flows. The electrical conductivity in the groundwater increases towards the NE-SW in the direction of flow. The Gibbs diagram and ionic relationships (molar ratios) between major ions ascribed the degree of correlation and difference in enrichment to rock water interaction, ion exchange, and the absence of carbonate minerals in TMG rocks. Groundwater samples revealed a similar isotopic composition of stable isotopes (δ18O and δ 2H) across the summer and winter seasons. These similarities indicate a hydraulic connection between different aquifers with no seasonal variability. The groundwater isotopic signatures indicated water that recharged prior to an evaporation effect. This is attributed to the circulation of water through fractures, joints, and faults in the form of direct recharge. The Kabeljous River showed an enriched δ18O and δ2H composition that was least depleted in the winter season, whereas the upper Kabeljous River revealed a similar isotopic signature to groundwater samples (highly depleted). This confirmed the presence of groundwater-surface water interaction through groundwater discharge into the river channel upstream and its non existence downstream. This study showed that hydrogeochemical and stable isotope analyses are effective in the assessment and characterisation of water sources, chemistry, interaction and related processes
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Hydrogeology to the Faculty of Science, School of Geoscience, University of the Witwatersrand, Johannesburg, 2021